2022
DOI: 10.1002/admi.202102322
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Textiles Enabled by Simultaneous Interaction with Infrared and Microwave Electromagnetic Waves

Abstract: Conventional textiles keep the body warm and provide an aesthetic appearance for human beings, while they are insufficient for military and civil applications in harsh environments. Multifunctional textiles that are capable of creating infrared (IR) camouflage, electromagnetic interference (EMI) shielding, and personal warming by interacting with both IR and microwave electromagnetic waves (EMWs) are developed. The inorganic–organic polytetrafluoroethylene (PTFE)/Ag/PTFE (IO‐PAP) building blocks are deposited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Wang et al 117 proposed an inorganic−organic polytetrafluoroethylene (PTFE)/Ag/PTFE (IO-PAP) blocks that can simultaneously block infrared radiation and shield EMI, besides showing personal warming. PTFE and Ag were deposited on PU-coated textiles using an eco-friendly magnetic sputtering technique.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 99%
“…Wang et al 117 proposed an inorganic−organic polytetrafluoroethylene (PTFE)/Ag/PTFE (IO-PAP) blocks that can simultaneously block infrared radiation and shield EMI, besides showing personal warming. PTFE and Ag were deposited on PU-coated textiles using an eco-friendly magnetic sputtering technique.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 99%
“…However, its shielding mechanism was reflection. 32 Shi et al put forward an absorption bishielding opaque material with an SE > 40 dB at the X band, which did not meet the criterion of g s ≥ 1 and SE R < 3.01. 33 The material in ref 34 had a microwave absorption over 90% in 3−8 GHz and a very low IR emissivity of about 0.2 at 8−14 μm, but it was opaque and inflexible.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many efforts have been made on the design of multifunctional materials, which can simultaneously shield microwave and IR radiation based on conventional materials , and MMAs. , With the help of melamine-based hybrid foam, an IR and EMI shielding opaque material with ultralow IR emissivity (∼0.1) at 3–14 μm and an ultrahigh SE = 47 dB at the X band was proposed. However, its shielding mechanism was reflection . Shi et al put forward an absorption bishielding opaque material with an SE > 40 dB at the X band, which did not meet the criterion of g s ≥ 1 and SE R < 3.01 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Zhou et al 41 found that the coated fabric showed good infrared camouflage and excellent electromagnetic interference (EMI) camouflage effect under the synergistic effect of polyaniline, silverplated structure, and nano zinc oxide. Wang et al 42 proposed depositing inorganic organic polytetrafluoroethylene/Ag/polytetrafluoroethylene components on polyurethane coated textiles using magnetron sputtering technology. A smooth and durable Ag layer was grown, which could avoid the large roughness and few connections between fibers in traditional textiles.…”
mentioning
confidence: 99%